Human chorionic gonadotropin and GnRH effects on pregnancy survival in pregnant cows and resynchronized pregnancy rates - B.S. Buttery; M.G. Burns; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 2007)
Experiments have shown human chorionic gonadotropin (hCG) to be more effective than gondadotropin releasing hormone (GnRH) as a means to ovulate follicles. Experiment 1 determined the effects of replacing the first injection of GnRH (day 7) with hCG or saline in a Resynch-Ovsynch protocol on pregnancy rates in cows subsequently diagnosed not pregnant and pregnancy survival in cows subsequently diagnosed pregnant (day 0). A second study determined the ovulation potential of hCG compared with GnRH and saline (Exp. 2). In Exp. 1, cows in 4 herds were assigned randomly based on lactation number, number of previous AI, and last test-day milk yield to treatments of 1,000 IU of hCG, 100 Î¼g of GnRH, or left as untreated controls 7 days before pregnancy diagnosis. Cows found not pregnant were given PGF2α(day 0), then inseminated 72 hours later, concurrent with a GnRH injection (3 herds) or given GnRH 16 to 24 hours before AI at 72 hours (1 herd). Timed AI pregnancy rates tended (P = 0.08) to be reduced by saline (12.9%; n = 505) compared with GnRH (17.9%; n = 703) but not hCG (16.5%; n = 541). Among pregnant cows treated, pregnancy survival 4 to 9 weeks after initial pregnancy diagnosis differed among herds (P<0.001); but in 1 herd, GnRH reduced pregnancy survival, whereas hCG seemed to increase survival compared with control. Only small differences were detected in the other 3 herds, except for a slight negative effect of hCG compared with control in 1 herd. Ovarian structures were monitored in herd 1 by using transrectal ultrasonography 0 and 7 days after treatment with hCG, GnRH, or saline (Exp. 2). A tendency for a treatment x pregnancy status interaction (P = 0.07) was detected. Incidences of ovulation in nonpregnant cows were: hCG (51.6%; n = 126), GnRH (46.1%; n = 102), and control (28.1%; n = 96), whereas those in pregnant cows were: hCG (59.3%; n = 59), GnRH (24.5%; n = 49), and saline (6.9%; n = 58). We concluded that: 1) initiating a Resynch-Ovsynch protocol 7 days before pregnancy diagnosis with saline reduced timed AI pregnancy rates (Exp. 1); 2) in pregnant cows treated with GnRH, pregnancy survival was slightly reduced in 1 of 4 herds (Exp. 1); and 3) incidence of new corpus luteum (CL) was greater after hCG than GnRH in pregnant cows but not in nonpregnant cows (Exp. 2).; Dairy Day, 2007, Kansas State University, Manhattan, KS, 2007; Dairy Research, 2007 is known as Dairy Day, 2007
Keywords: Dairy Day; 2007; Kansas Agricultural Experiment Station contribution; no. 08-127-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 984; Dairy; hCG; GnRH; Pregnancy rates